Psychometric properties of the Family Satisfaction Scale to Uruguayan families - Costa-Ball, Cesar; Cracco, Cecilia (Anales de Psicología / Annals of Psychology, 2021)
The aim of the present study was to analyze the psychometric properties of the Family Satisfaction Scale (Olson, 2010). Family satisfaction has been evaluated by clinicians and researchers, particularly in relation to the Circumplex Model of Marital and Family Systems. Despite its widespread use, there are few adaptations to Spanish. Based on the translation process and preliminary reliability data, an instrumental study was conducted with a sample of 385 families from the general population, with the aim of obtaining evidence supporting the validity and reliability of the scale. The results of the confirmatory factor analysis show a good adjustment of the data to a one-dimensional structure, with a high reliability index. The external validity analyzes were performed with the rest of the FACES IV scales, with expected results according to the theoretical model. To obtain criterion validity data, we compared the results obtained in a clinical sample (N = 77) with an equivalent subsample of the participants, finding significant differences between the two groups. It is concluded that the Family Satisfaction Scale is a valid and reliable technique for the assessment of satisfaction in Uruguayan families.